Damping cloth polishing pad and preparation method thereof
By using a specific polishing layer in the damping cloth polishing pad and combining the damping cloth layer, the problem of short service time and easy damage in the prior art is solved, and a more stable and durable polishing effect is achieved, and the quality of semiconductor devices is improved.
Patent Information
- Application Number
- CN202510043072.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing damping cloth polishing pads have a short service life and are prone to damage, resulting in unstable polishing effect and may introduce surface defects, affecting the quality of semiconductor devices.
A polishing layer consisting of nylon, polycarbonate, dispersant, silane coupling agent, first compatibilizer, polyphenylene sulfide and fillers (diamond powder, calcium silicate and magnesium oxide) is used to form a wear-resistant and heat-resistant polishing pad.
It extends the service life of the polishing pad, improves the stability and consistency of the polishing effect, reduces the occurrence of surface defects, and improves the quality and yield of semiconductor devices.
Smart Images

Figure BDA0005237520100000061 
Figure BDA0005237520100000071 
Figure BDA0005237520100000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of damping cloth polishing pad processing, and more specifically, to a damping cloth polishing pad and a preparation method thereof. Background Art
[0002] Damping cloth polishing pad is a polishing material with damping effect, usually composed of damping cloth and polishing layer, and is usually used for polishing semiconductors. The reason is that the damping cloth polishing pad has a fine texture and a soft surface, which can effectively avoid scratches or damage to the surface of semiconductor materials during the polishing process. At the same time, its porous structure can accommodate polishing liquid, improve the polishing effect, and make the polished semiconductor surface smoother and flatter.
[0003] However, in the actual production process, due to the continuous friction and wear between the damping cloth polishing pad and the semiconductor material during the polishing process, the polishing pad often shows obvious wear marks after a period of use. This not only leads to unstable polishing effects, but may also introduce additional surface defects, thus affecting the quality of semiconductor devices. Therefore, in order to ensure the stability and consistency of the polishing process, the polishing pad needs to be replaced regularly to maintain its optimal polishing performance and durability. Summary of the invention
[0004] In order to solve the problem that the existing damping cloth has a short service life and is easily damaged, the present application provides a damping cloth polishing pad and a preparation method thereof.
[0005] In a first aspect, the present application provides a damping cloth polishing pad, which adopts the following technical solution: A damping cloth polishing pad comprises a damping cloth layer and a polishing layer, wherein the polishing layer is prepared from the following raw materials in percentage by weight: Nylon 40-50% Polycarbonate 10-15% Dispersant 4-8% Silane coupling agent 1-2% First compatibilizer 1-1.5% Polyphenylene sulfide 4-8% The rest is filler The filler is composed of diamond powder, calcium silicate and magnesium oxide.
[0006] By adopting the above technical solution, the damping cloth layer and the polishing layer are combined, which not only ensures the flexibility and adaptability of the polishing pad, but also achieves a good polishing effect through the special formula of the polishing layer, while also ensuring that the polishing layer has good wear resistance, is not easy to be damaged, can be used for a long time, and reduces the frequency of replacement. In addition, the enhanced wear resistance makes it difficult for the polishing layer to produce particles and waste during polishing, reduces the fluctuation of the polishing effect caused by wear, ensures the consistency and stability of the polishing process, and is conducive to improving the quality of semiconductor devices. At the same time, the polishing layer helps to reduce surface defects such as scratches and pits that may occur during the polishing process, further improving the yield and quality of semiconductor devices.
[0007] Among them, nylon has excellent tear strength and wear resistance, while polyphenylene sulfide has good chemical stability. The combination of the two enables the polishing pad to withstand greater friction and wear during use, thereby extending its service life. The damping polishing pad will generate heat due to friction during the polishing process, and the heat generated is also one of the reasons for the accelerated damage of the polishing pad. The addition of polycarbonate in the present application enhances the thermal stability and mechanical strength of the polishing pad. During the polishing process, the polishing pad can maintain a stable shape and size, and is not easily deformed or damaged due to high temperature or high pressure, thereby ensuring the stability and consistency of the polishing effect. The synergistic effect of the dispersant and the silane coupling agent enables the filler in the polishing layer to be evenly dispersed in the matrix, avoiding the occurrence of agglomeration. This not only improves the uniformity and density of the polishing layer, but also reduces the fluctuation of the polishing effect caused by uneven distribution of the filler.
[0008] At the same time, the diamond powder in the polishing layer acts as a hard filler, which can improve the polishing efficiency and polishing accuracy. The high hardness of the diamond powder enables it to more effectively remove the tiny bumps and defects on the surface of the semiconductor material, thereby obtaining a smoother and more uniform polishing surface. Calcium silicate and magnesium oxide, as auxiliary fillers, play a role in enhancing the hardness and wear resistance of the polishing layer. At the same time, their tiny particle structure promotes the uniform distribution of the polishing liquid, further improving the polishing effect.
[0009] Preferably, the weight ratio of the diamond powder, the calcium silicate and the magnesium oxide is (5-6):(1-3):3.
[0010] By adopting the above technical solution, the weight ratio of diamond powder, calcium silicate and magnesium oxide is optimized to further improve the polishing effect. Among them, the content of diamond powder is relatively high, which can provide sufficient polishing force and ensure the improvement of polishing efficiency and precision. The weight of calcium silicate and magnesium oxide is relatively small, which can form a good match with diamond powder and magnesium oxide, improve the overall strength and stability of the polishing layer, help to extend the service life of the polishing pad, and reduce the replacement frequency and cost.
[0011] Preferably, the average particle size of the diamond powder is 50-100 nm, the average particle size of the calcium silicate is 150-200 nm, and the average particle size of the magnesium oxide is 50-250 nm.
[0012] By adopting the above technical solution, the average particle size of diamond powder, calcium silicate and magnesium oxide is optimized, and the polishing accuracy, efficiency and durability of the damping cloth polishing pad can be further improved. The average particle size of the diamond powder used in the present application is 50-100nm, which is conducive to the damping polishing pad to quickly and effectively remove tiny defects and flaws on the surface of the semiconductor material during the polishing process, thereby improving the polishing accuracy and finish. The average particle size of the calcium silicate used in the present application is 150-200nm, which helps the polishing pad to maintain a stable shape and size during use and is not easily damaged by wear. The average particle size of the magnesium oxide used in the present application is 50-250nm, which can enhance the abrasive capacity of the polishing layer. During the polishing process, it can more effectively remove the roughness and scratches on the surface of the semiconductor material.
[0013] Preferably, the degree of polymerization of the polyphenylene sulfide is 500-1500.
[0014] By adopting the above technical solution, the degree of polymerization of polyphenylene sulfide is optimized, so that the mechanical strength of polyphenylene sulfide is improved and it is easy to process. In the polishing pad, polyphenylene sulfide with high mechanical strength can provide better wear resistance and tear resistance, thereby extending the service life of the polishing pad, which is of great significance in helping to reduce the frequency of replacing the polishing pad and reducing production costs.
[0015] Preferably, the polycarbonate is composed of bisphenol A polycarbonate and glass fiber modified polycarbonate in a weight ratio of (2-5):7.
[0016] By adopting the above technical solution, the type and amount of polycarbonate are optimized, and the heat resistance, mechanical strength and wear resistance of the polishing layer are further improved, which is conducive to improving the polishing effect and durability of the polishing layer. Among them, bisphenol A type polycarbonate has good heat resistance and can maintain stable performance in a high temperature environment. During the polishing process, the polishing pad will be affected by high temperature and friction, and the heat resistance of bisphenol A type polycarbonate helps the polishing pad maintain a stable shape and size, and is not easy to deform or break. Glass fiber modified polycarbonate further improves the heat resistance and scratch resistance of polycarbonate by introducing silicone components, making the polishing pad more stable and reliable during manufacturing and use.
[0017] At the same time, the use of bisphenol A polycarbonate and glass fiber modified polycarbonate together makes the polishing layer have a smoother and more uniform surface, can provide a better polishing effect, and can be applied to more types of semiconductor materials, especially materials with higher polishing requirements.
[0018] Preferably, the first compatibilizer is composed of ethylene-acrylate-maleic anhydride copolymer, bisphenol A glycidyl ether and organic montmorillonite in a weight ratio of (4-6):1:(2-3).
[0019] By adopting the above technical solution, the compatibility of nylon, polycarbonate, polyphenylene sulfide and filler is further promoted, thereby improving the tensile strength, impact strength, wear resistance and toughness of the polishing pad, helping to reduce the breakage and deformation of the polishing pad during the polishing process and extend its service life. At the same time, the three are used in synergy to improve the compatibility and interface bonding between materials, so that the polishing pad can act more evenly on the surface of the semiconductor material during the polishing process, reducing the occurrence of uneven polishing and surface defects.
[0020] Among them, ethylene-acrylate-maleic anhydride copolymer has excellent compatibility and adhesion, and can form a good interface with polymer materials such as nylon and polycarbonate. At the same time, the epoxidized structure of bisphenol A glycidyl ether can react chemically with these polymers, further enhancing the interaction between them. Organic montmorillonite has strong adsorption capacity and good dispersibility, which can significantly improve the dispersibility and stability of fillers such as diamond powder, calcium silicate and magnesium oxide in the polymer matrix, prevent the occurrence of agglomeration and sedimentation, and thus improve the polishing effect of the polishing layer.
[0021] Preferably, the damping fabric layer is prepared from raw materials having the following weight percentages: Nylon 40-50% Ethylene-vinyl acetate copolymer 10-15% Second compatibilizer 1-2% Toughener 0.5-1% The balance is polyethylene.
[0022] Through the synergistic effect of nylon, ethylene-vinyl acetate copolymer, second compatibilizer, toughening agent and polyethylene, the damping cloth layer has moderate strength, elasticity and toughness, providing the necessary structural support and strength for the entire polishing pad, ensuring that the polishing pad can maintain a stable shape during use and is not easily deformed or damaged. The damping cloth layer has a certain elasticity, which can buffer and adjust the polishing pressure during the polishing process, helping to avoid scratches or damage on the surface of the semiconductor material caused by excessive polishing pressure.
[0023] The nylon in the damping cloth layer has the same composition as the nylon in the polishing layer, and uniform nylon is used as the main material. During the production process of the damping cloth polishing pad, the damping cloth layer and the polishing layer may be combined together by casting, hot pressing, bonding or other processing methods. According to the principle of similarity and compatibility, the damping cloth layer and the polishing layer are easier to achieve tight fusion during the processing, thereby ensuring the stability of the connection, helping to reduce the delamination or falling off between the damping cloth layer and the polishing layer during the polishing process, ensuring the structural stability of the polishing pad during the polishing process, and the stably connected polishing pad can better transmit the polishing force, thereby improving the polishing efficiency.
[0024] Preferably, the second compatibilizer is polyethylene grafted maleic anhydride.
[0025] By adopting the above technical solution, the compatibility of nylon, ethylene-vinyl acetate copolymer and polyethylene is further promoted, so that the above raw materials can be mixed more evenly to form a stable damping cloth layer structure, thereby improving the strength and hardness of the damping cloth layer, helping the damping cloth layer to better resist wear and deformation during the polishing process and extending the service life of the polishing pad.
[0026] In a second aspect, the present application provides a method for preparing a damping cloth polishing pad, using the following technical solution: A method for preparing a damping cloth polishing pad comprises the following preparation steps: S1, mixing nylon, ethylene-vinyl acetate copolymer, a second compatibilizer, a toughening agent and polyethylene, and then performing melt spinning to prepare a damping fabric layer; S2, mixing nylon, polycarbonate, dispersant, silane coupling agent, first compatibilizer, polyphenylene sulfide and filler, melt-casting them on the surface of the damping cloth layer to form a polishing layer, and then cutting them to obtain a damping cloth polishing pad.
[0027] The damping cloth layer prepared by the melt spinning process has a uniform and compact fiber structure, which helps to enhance the overall stability and strength of the damping cloth layer. The polishing layer is melt-casted onto the surface of the damping cloth layer and tightly combined with the damping cloth layer to form a stable double-layer structure, so that the polishing layer of the damping cloth polishing pad has excellent polishing performance, can evenly transmit polishing force, reduce defects and damage during polishing, help improve polishing efficiency, and shorten production cycles. At the same time, it ensures that the polishing layer can resist friction and wear during use and prolong its service life.
[0028] Preferably, the thickness ratio of the damping cloth layer to the polishing layer is 10:(0.2-0.8).
[0029] By adopting the above solution, the thickness ratio of the damping cloth layer and the polishing layer is optimized, so that the polishing pad can better resist wear and deformation during use and extend its service life. At the same time, it not only ensures sufficient polishing ability, but also avoids uneven polishing caused by excessive thickness and insufficient wear resistance caused by excessive thinness. And this thickness design enables the polishing pad to evenly transmit polishing force during the polishing process, reduce defects and damage on the polishing surface, and improve the consistency and stability of the polishing effect.
[0030] In summary, this application has the following beneficial effects: 1. In the present application, by preparing a polishing layer with nylon, polycarbonate, dispersant, silane coupling agent, first compatibilizer, polyphenylene sulfide and filler, the wear resistance of the polishing pad can be improved, its service life can be extended, and the consistency and stability during the polishing process can be maintained, and the fluctuation of the polishing effect caused by the wear of the polishing pad can be reduced. Among them, the filler is composed of diamond powder, calcium silicate and magnesium oxide, which can significantly improve the polishing efficiency, precision and durability of the damping cloth polishing pad. DETAILED DESCRIPTION Example
[0031] Nylon was purchased from Dongguan Weide Plastic Raw Materials Co., Ltd. The manufacturer is Asahi Kasei of Japan, and the brand number is 14G33.
[0032] Ethylene-vinyl acetate copolymer was purchased from Guangzhou Jiushun New Materials Co., Ltd. The brand is DuPont of the United States and the grade is 265A.
[0033] Polyethylene was purchased from Dongguan Julong Plastic Raw Materials Co., Ltd. The brand is SABIC and the grade is 3H673.
[0034] Polyethylene grafted maleic anhydride was purchased from Longcheng New Materials Business Department, Changping, Dongguan City. The brand is Arkema and the grade is 18341.
[0035] Ethylene-acrylate-maleic anhydride copolymer was purchased from Aeruifu (Shanghai) New Material Technology Co., Ltd. with the brand name SK and model number 4403.
[0036] Ethylene octene copolymer was purchased from Ningbo Keming Plastic Chemical Co., Ltd. The brand is Dow, USA, and the model is 8180.
[0037] Polymethyl methacrylate was purchased from Dongguan Hongkuo Plastic Co., Ltd. The brand is Thai Dow and the model is 8173.
[0038] The maleic anhydride grafted EPDM rubber was purchased from Hengtai Plastic Raw Materials Business Department in Zhangmutou, Dongguan City, with the brand name Shenghao Rubber and Plastic.
[0039] Organic montmorillonite was purchased from Jiayuan Mineral Products Processing Plant in Lingshou County with a mesh size of 325 meshes.
[0040] Bisphenol A polycarbonate was purchased from Shanghai Myrel Biochemical Technology Co., Ltd. with the product number M69009.
[0041] Glass fiber modified polycarbonate was purchased from Dongguan Xingxiang New Materials Co., Ltd. The brand is Japan Idemitsu and the grade is PCG2510.
[0042] Example 1 A damping cloth polishing pad is prepared by the following preparation method: S1. Mix 400g of nylon, 150g of ethylene-vinyl acetate copolymer, 20g of the second compatibilizer (polyethylene grafted maleic anhydride), 10g of toughening agent (ethylene octene copolymer) and 420g of polyethylene, and then perform melt spinning to prepare a damping cloth layer; S2. Mix 400g of nylon, 150g of polycarbonate, 80g of dispersant (stearic acid), 20g of silane coupling agent (vinyl trimethoxy silane), 15g of the first compatibilizer (ethylene-acrylate-maleic anhydride copolymer), 80g of polyphenylene sulfide and 255g of filler, melt-cast onto the surface of the damping cloth layer to form a polishing layer, and then cut to obtain a damping cloth polishing pad.
[0043] The degree of polymerization of polyphenylene sulfide is 500.
[0044] The filler is composed of diamond powder, calcium silicate and magnesium oxide in a weight ratio of 5:1:3, the average particle size of the diamond powder is 50-70nm, the average particle size of the calcium silicate is 150-170nm, and the average particle size of the magnesium oxide is 50-100nm.
[0045] The thickness ratio of the damping cloth layer to the polishing layer is 10:0.2.
[0046] The difference between Example 2-3 and Example 1 is that the types of raw materials, amounts and experimental parameters for preparing the damping cloth polishing pad are different. The specific differences are shown in Table 1: Table 1 Types of raw materials, amounts and experimental parameters for preparing damping cloth polishing pads in Examples 1-3 In Example 2, the average particle size of the diamond powder is 71-90 nm, the average particle size of the calcium silicate is 171-190 nm, and the average particle size of the magnesium oxide is 101-200 nm.
[0047] In Example 3, the average particle size of the diamond powder is 91-100 nm, the average particle size of the calcium silicate is 191-200 nm, and the average particle size of the magnesium oxide is 201-250 nm.
[0048] In Example 2, the thickness ratio of the damping cloth layer to the polishing layer is 10:0.6.
[0049] In Example 3, the thickness ratio of the damping cloth layer to the polishing layer is 10:0.8.
[0050] Example 4 A damping cloth polishing pad. The difference between this embodiment and embodiment 1 is that the weight ratio of diamond powder, calcium silicate and magnesium oxide is 5:5:3.
[0051] Example 5 A damping cloth polishing pad. The difference between this embodiment and embodiment 1 is that the weight ratio of diamond powder, calcium silicate and magnesium oxide is 5:1:5.
[0052] Example 6 A damping cloth polishing pad, the difference between this embodiment and embodiment 4 is that: the first compatibilizer is composed of ethylene-acrylate-maleic anhydride copolymer, bisphenol A glycidyl ether and organic montmorillonite in a weight ratio of 4:1:2.
[0053] Example 7 A damping cloth polishing pad, the difference between this embodiment and embodiment 1 is that: the first compatibilizer is composed of ethylene-acrylate-maleic anhydride copolymer, bisphenol A glycidyl ether and organic montmorillonite in a weight ratio of 4:1:3.
[0054] Example 8 A damping cloth polishing pad. The difference between this embodiment and embodiment 4 is that the first compatibilizer is composed of ethylene-acrylate-maleic anhydride copolymer and bisphenol A glycidyl ether in a weight ratio of 4:1.
[0055] Example 9 A damping cloth polishing pad. The difference between this embodiment and embodiment 4 is that the first compatibilizer is composed of bisphenol A glycidyl ether and organic montmorillonite in a weight ratio of 1:2.
[0056] Example 10 A damping cloth polishing pad. The difference between this embodiment and embodiment 1 is that the average particle size of diamond powder is 50-70nm, the average particle size of calcium silicate is 50-70nm, and the average particle size of magnesium oxide is 50-70nm.
[0057] Embodiment 11 A damping cloth polishing pad, the difference between this embodiment and embodiment 1 is that the average particle size of the diamond powder is 150-200nm.
[0058] Example 12 A damping cloth polishing pad. The difference between this embodiment and embodiment 1 is that the average particle size of the calcium silicate is 50-70 nm.
[0059] Embodiment 13 A damping cloth polishing pad, the difference between this embodiment and embodiment 1 is that the average particle size of magnesium oxide is 50-70nm.
[0060] Embodiment 14 A damping cloth polishing pad. The difference between this embodiment and embodiment 1 is that the polycarbonate is composed of bisphenol A polycarbonate and glass fiber modified polycarbonate in a weight ratio of 2:7.
[0061] Embodiment 15 A damping cloth polishing pad, the difference between this embodiment and embodiment 6 is that the polycarbonate is composed of bisphenol A type polycarbonate and glass fiber modified polycarbonate in a weight ratio of 5:7 Comparative Example Comparative Example 1 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that silicon dioxide is used instead of calcium silicate.
[0062] Comparative Example 2 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that zinc oxide is used instead of magnesium oxide.
[0063] Comparative Example 3 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that polyurethane is used instead of polycarbonate.
[0064] Polyurethane was purchased from Dongguan Yingxiang Plastic Raw Materials Co., Ltd. The brand is Covestro of Germany and the model is 3491A.
[0065] Comparative Example 4 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that polyurethane is used instead of polyphenylene sulfide.
[0066] Polyurethane was purchased from Dongguan Yingxiang Plastic Raw Materials Co., Ltd. The brand is Covestro of Germany and the model is 3491A.
[0067] Comparative Example 5 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that the filler is composed of diamond powder and calcium silicate in a weight ratio of 5:1.
[0068] Comparative Example 6 A damping cloth polishing pad. The difference between this comparative example and Example 1 is that the filler is composed of diamond powder and magnesium oxide in a weight ratio of 5:3.
[0069] Detection method / test method Wear resistance test: A UNIPOL-1200S CMP test machine was used for polishing experiments, using Fujimi 3900 polishing liquid, a polishing pad diameter of 200 mm, and a silicon wafer diameter of 2 inches.
[0070] The polishing parameters are as follows: polishing pressure 4 psi, polishing speed 100 rpm, polishing liquid flow rate 200 mL / min, and polishing time 10 min.
[0071] The polishing pads of Examples 1-15 and Comparative Examples 1-5 were polished for 3 hours, then washed and dried, and the weight changes of the polishing pads before and after polishing were recorded.
[0072] Polishing test: A UNIPOL-1200S CMP test machine was used for polishing experiments, using Fujimi 3900 polishing liquid, a polishing pad diameter of 200 mm, and a silicon wafer diameter of 2 inches.
[0073] The polishing parameters are as follows: polishing pressure 4 psi, polishing speed 100 rpm, polishing liquid flow rate 200 mL / min, and polishing time 10 min.
[0074] The wafer mass before and after polishing is weighed using a METTLER TOLETO precision electronic balance, converted into wafer thickness, and the material removal rate during polishing, i.e., the polishing rate, is calculated. The material thickness removed by polishing per unit time is defined as the material removal rate, and the calculation formula is as follows: Polishing rate (nm / min) = (W0-W i ) / (p w *S w *t)*10 7 Where W0 is the mass of the silicon wafer before polishing (g), W i is the mass of the silicon wafer after polishing (g), p w is the density of silicon wafer material (g / cm 3 ), S w is the surface area of silicon wafer (cm 2 ), t is the polishing time (min).
[0075] Polishing effect: Observe the smoothness of the polished wafer surface during the polishing test and observe whether there are scratches. The experimental data is shown in Table 2: Table 2 Experimental data of Examples 1-14 and Comparative Examples 1-6 By comparing Example 1 with Comparative Example 1-2, the weight change value of the polishing pad before and after polishing in Comparative Example 1-2 is greater than that in Example 1, and the polishing rate of Comparative Example 1-2 is lower than that in Example 1; By comparing Example 1 with Comparative Examples 5-6, the weight change value of the polishing pad before and after polishing in Comparative Example 5-6 is greater than that in Example 1, and the polishing rate of Comparative Example 5-6 is lower than that of Example 1; and scratches appear on the surface of the wafer of Comparative Example 5-6; It can be seen from Example 1, Comparative Examples 1-2, and 4-5 that the combined use of diamond powder, calcium silicate, and magnesium oxide is beneficial to improving the wear resistance, polishing rate, and polishing effect of the damping cloth polishing pad.
[0076] Comparing Example 1 with Comparative Examples 3-4, the weight change of the polishing pad before and after polishing in Comparative Example 3-4 is greater than that in Example 1, and the polishing rate of Comparative Example 3-4 is lower than that of Example 1; and scratches appear on the surface of the chip in Comparative Example 3-4, indicating that the use of polycarbonate, polyphenylene sulfide, nylon and filler is beneficial to improving the wear resistance, polishing rate and polishing effect of the damping cloth polishing pad.
[0077] Comparing Example 1 with Example 4-5, the weight change of the polishing pad before and after polishing in Example 4-5 is greater than that in Example 1, and the polishing rate of Example 4-5 is lower than that of Example 1, indicating that optimizing the dosage of diamond powder, calcium silicate and magnesium oxide is beneficial to improving the wear resistance and polishing rate of the damping cloth polishing pad.
[0078] By comparing Example 1 with Example 6-7, the weight change value of the polishing pad before and after polishing in Example 6-7 is smaller than that in Example 1, and the polishing rate of Example 6-7 is higher than that of Example 1; By comparing Example 4 with Examples 8-9, the weight change value of the polishing pad before and after polishing in Example 8-9 is greater than that in Example 4, and the polishing rate of Example 8-9 is lower than that of Example 4; It can be seen from Examples 1 and 6-7, and Examples 4 and 8-9 that optimizing the type and amount of the first compatibilizer is beneficial to improving the wear resistance and polishing rate of the damping cloth polishing pad.
[0079] Comparing Example 1 with Examples 10-13, the weight change of the polishing pad before and after polishing in Examples 10-13 is greater than that in Example 1, and the polishing rate of Examples 10-13 is lower than that in Example 1, indicating that optimizing the average particle size of diamond powder, the average particle size of calcium silicate and the average particle size of magnesium oxide is beneficial to improving the wear resistance and polishing rate of the damping cloth polishing pad.
[0080] By comparing Example 1 with Example 14, the weight change value of the polishing pad before and after polishing in Example 1 is greater than that in Example 14, and the polishing rate of Example 1 is lower than that of Example 14; By comparing Example 4 with Example 15, the weight change value of the polishing pad before and after polishing in Example 4 is greater than that in Example 15, and the polishing rate of Example 4 is lower than that of Example 15; It can be seen from Examples 1 and 14, and Examples 4 and 15 that optimizing the type and amount of polycarbonate is beneficial to improving the wear resistance and polishing rate of the damping cloth polishing pad.
[0081] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A damping cloth polishing pad, comprising a damping cloth layer and a polishing layer, characterized in that: The polishing layer is prepared from the following raw materials in weight percentage: Nylon 40-50% Polycarbonate 10-15% Dispersant 4-8% Silane coupling agent 1-2% First compatibilizer 1-1.5% Polyphenylene sulfide 4-8% The rest is filler The filler is composed of diamond powder, calcium silicate and magnesium oxide.
2. A damping cloth polishing pad according to claim 1, characterized in that: The weight ratio of the diamond powder, the calcium silicate and the magnesium oxide is (5-6): (1-3):
3.
3. A damping cloth polishing pad according to claim 2, characterized in that: The polymerization degree of the polyphenylene sulfide is 500-1500.
4. A damping cloth polishing pad according to claim 1, characterized in that: The polycarbonate is composed of bisphenol A polycarbonate and glass fiber modified polycarbonate in a weight ratio of (2-5):
7.
5. A damping cloth polishing pad according to claim 4, characterized in that: The first compatibilizer is composed of ethylene-acrylate-maleic anhydride copolymer, bisphenol A glycidyl ether and organic montmorillonite in a weight ratio of (4-6):1:(2-3).
6. A damping cloth polishing pad according to claim 4, characterized in that: The average particle size of the diamond powder is 50-100 nm, the average particle size of the calcium silicate is 150-200 nm, and the average particle size of the magnesium oxide is 50-250 nm.
7. A damping cloth polishing pad according to claim 1, characterized in that: The damping fabric layer is prepared from the following raw materials in weight percentage: Nylon 40-50% Ethylene-vinyl acetate copolymer 10-15% Second compatibilizer 1-2% Toughener 0.5-1% The balance is polyethylene.
8. The damping cloth polishing pad according to claim 1, characterized in that: The second compatibilizer is polyethylene grafted with maleic anhydride.
9. A method for preparing a damping cloth polishing pad according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1, mixing nylon, ethylene-vinyl acetate copolymer, a second compatibilizer, a toughening agent and polyethylene, and then performing melt spinning to prepare a damping fabric layer; S2, mixing nylon, polycarbonate, dispersant, silane coupling agent, first compatibilizer, polyphenylene sulfide and filler, melt-casting them on the surface of the damping cloth layer to form a polishing layer, and then cutting them to obtain a damping cloth polishing pad.
10. The method for preparing a damping cloth polishing pad according to claim 9, characterized in that: The thickness ratio of the damping cloth layer to the polishing layer is 10:(0.2-0.8).
Citation Information
Patent Citations
Abrasive article and method of making the same
CN109789537A
Polishing wheel for processing hard and brittle material and preparation method thereof
CN111775071A
Preparation method of damping fabric polishing pad
CN112428165A
Damping cloth for polishing surface of optical element and production process of damping cloth
CN116810665A
Motor valve and pressure reducing system
JP2005030439A
Cited By
Production process of CMP (Chemical Mechanical Polishing) pad with semi-continuous surface thickness preparation
CN120962536A